2021
DOI: 10.1016/j.rbmo.2020.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles, microRNA and the preimplantation embryo: non-invasive clues of embryo well-being

Abstract: • Extracellular vesicles and microRNA comprise the blastocyst secretome • Vesicles are elevated for blastocysts with diminished developmental competence • Vesicles may be rapidly detected by nanoparticle tracking analysis and flow cytometry • Ailing blastocysts release greater variety and amounts of microRNA • Studies have yet to show clear correlation between microRNA and embryo competence RBMO VOLUME 00 ISSUE 0 2020

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 111 publications
(246 reference statements)
0
20
0
Order By: Relevance
“…Extracellular miRNAs and extracellular vesicles (EVs) of embryonic origin are of particular interest owing to their potential application in the ongoing initiative aimed at improving embryo transfer outcomes during assisted reproduction [reviewed by Hawke et al (2020)]. Clinical studies are now reporting detection of nearly 150 miRNAs within spent media microdroplets used to culture human blastocysts (Russell et al, 2020); miRNAs have also been identified within the spent media used to culture bovine (Kropp et al, 2014;Kropp and Khatib, 2015;Gross et al, 2017b;Lin et al, 2019a,b) and murine (Heidari et al, 2019) pre-implantation embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular miRNAs and extracellular vesicles (EVs) of embryonic origin are of particular interest owing to their potential application in the ongoing initiative aimed at improving embryo transfer outcomes during assisted reproduction [reviewed by Hawke et al (2020)]. Clinical studies are now reporting detection of nearly 150 miRNAs within spent media microdroplets used to culture human blastocysts (Russell et al, 2020); miRNAs have also been identified within the spent media used to culture bovine (Kropp et al, 2014;Kropp and Khatib, 2015;Gross et al, 2017b;Lin et al, 2019a,b) and murine (Heidari et al, 2019) pre-implantation embryos.…”
Section: Introductionmentioning
confidence: 99%
“…These associations enhance the stability of extracellular sncRNAs, allowing for their detection and use as biomarkers. Previous studies have profiled the sncRNA population in spermatozoa, seminal plasma, follicular fluid, and embryo culture medium, with an emphasis on identifying specific sets of sncRNAs whose relative abundance show strong correlation with reproductive diseases, infertility, or embryo developmental potential [ 119 , 210 , 211 , 212 , 213 ].…”
Section: Sncrnas In Sperm Seminal Plasma Follicular Fluid and Embryo Culture Medium As Biomarkers For Fertility And Embryo Development Pomentioning
confidence: 99%
“…Embryos cultured in vitro also produce extracellular vesicles that contain sncRNAs [ 230 ]. With constantly improving technologies, various miRNAs, piRNAs, and tRNA halves (tiRNAs) are detectable in spent culture media and suggest indicative potential for embryo quality, such as ploidy and pregnancy outcomes [ 212 , 213 , 230 , 231 , 232 , 233 , 234 , 235 ].…”
Section: Sncrnas In Sperm Seminal Plasma Follicular Fluid and Embryo Culture Medium As Biomarkers For Fertility And Embryo Development Pomentioning
confidence: 99%
“…Elective single embryo transfer is a method where the embryo with the best chance for survival is selected for implantation. With the selection of a single embryo, eSEP minimizes the complications that arise from a multiple pregnancy [ 3 ]. While the eSEP method lowers the number of viable pregnancies in comparison with double embryo transfer in a fresh cycle of in vitro fertilization (IVF), an additional frozen eSEP cycle minimizes this difference [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The best embryo is frequently selected based on morphological assessment, as this is a cost-effective, rapid, and non-invasive technique [ 3 , 5 ]. While it is widely used, this technique does not account for the possibility of genetic abnormalities, since there is no correlation between morphological traits and genetic material [ 6 ].…”
Section: Introductionmentioning
confidence: 99%